Doing your master's dissertation - Furseth, Inger; Everett, Euris Larry (London, England ; New Delhi : SAGE Publications Ltd., 2013)
With examples from real theses, useful action plans in each chapter and a range of practical tips that are often missed in other books, this is a step-by-step guide to help you excel in your Master's dissertation.
Help! how do i find a research topic? -- Overcoming barriers and getting started -- Basic rules of writing -- Who can help you? establishing support networks -- A guide for searching the literature -- Reviewing research literature -- How do i formulate research questions? -- Easier said than done -- choosing a suitable research design and method -- The art of keeping a steady course -- structuring the analysis -- Beginning and end -- introduction and conclusion -- Chaos and order -- editing and referencing -- When is it finished? checklist summary.
Paperback edition: subtitle "from start to finish" appears only on cover.
Includes bibliographical references (pages 150-152) and index.
Keywords: Dissertations, Academic; Academic writing; Academic writing; Dissertations, Academic; Dissertation; Wissenschaftliches Manuskript